Using entropy to construct and evaluate player's value and sustainable development model. Issue 6 (18th August 2019) - Chang, Che-Wei
Abstract: The value of an NBA basketball player varies at each crucial point in time, depending on the player's career and performance. This study constructs a player's value assessment model. The model comprises two parts. First, from an objective perspective, entropy is employed to measure each player's achievement in five categories rebounds, assists, steals, blocked shots, and scores. The total entropy assessment value is calculated and then combined with the players' scores to develop a player's value matrix to assess the relative value model among players of the same type.